Internal control weaknesses in a cooperative body: Malaysian experience - Shamsul Anuar, Abd Rahim; Anuar, Nawawi; Ahmad Saiful, Azlin Puteh Salin (Inderscience Enterprises Ltd., 2017)
The purpose of this study is to examine the current state of the internal control practices in the cooperative body, an organisation area that has always been neglected in governance empirical research. This study also provides recommendations to overcome those weaknesses. A case study approach was selected for this study by selecting one cooperative body as a case. This study employed document analysis as the method of data collection and the data were analysed by using the latest COSO Internal Control – Integrated Framework. This study found that the selected cooperative body had very poor internal control. There was low data integrity where too many errors were detected in both the financial and non-financial data, while its daily transactions were recorded by using manual tools but without proper security leading to possible fraud. Furthermore, the effort to automate the system by acquiring a new software program has miserably failed due to incompetency of the workforce. To worsen matters, the employees also did not appreciate the importance of internal control.